Geosmithia argillacea: An Emerging Cause of Invasive Mycosis in Human Chronic Granulomatous Disease - De Ravin, Suk See (Oxford University Press, 2011)
Background. Chronic granulomatous disease (CGD) is an inherited disorder of the nicotinamide adenine dinucleotide phosphate oxidase that leads to defective production of microbicidal superoxide and other oxidative radicals, resulting in increased susceptibility to invasive infections, especially those due to fungi. Methods. Geosmithia argillacea was identified from cultured isolates by genomic sequencing of the internal transcribed spacer region. Isolates previously identified as Paecilomyces variotii, a filamentous fungus closely resembling G. argillacea, were also examined. Results. We identified G. argillacea as the cause of invasive mycosis in 7 CGD patients. In 5 cases, the fungus had been previously identified morphologically as P. variotii. All patients had pulmonary lesions; 1 had disseminated lesions following inhalational pneumonia. Infections involved the chest wall and contiguous ribs in 2 patients and disseminated to the brain in 1 patient. Four patients with pneumonia underwent surgical intervention. All patients responded poorly to medical treatment, and 3 died. Conclusions. We report the first cases of invasive mycosis caused by G. argillacea in CGD patients. G. argillacea infections in CGD are often refractory and severe with a high fatality rate. Surgical intervention has been effective in some cases. G. argillacea is a previously underappreciated and frequently misidentified pathogen in CGD that should be excluded when P. variotii is identified morphologically.